Struktur Anatomi dan Jagung (Zea mays L.) yang Terserang Penyakit Bercak dan Karat - Riza Linda, Fittra Jeniria, Mukarlina (Jurnal Protobiont, 2015)
Spot and rust disease is a disease that most often attacks the leaves of the maize plant (Zea mays L.) Both of these diseases are caused by a different type of fungus infection that causes different symptoms. Symptoms of the disease, indicated by morphological change of the anatomical structure. This research is aimed at determining the anatomical structure of leaves of maize (Zea mays L.) infected with the spot and rust disease. The research was carried out from April to September 2014. The paraffin method is used in making preparations of transverse incision of leaves (Zea mays L.) that were stricken with the spot and rust disease. The result of the study showed a thickening of the epidermis tissue, increase in mesophyll cells and decrease in xylem diameter of transverse incision on the leaves of maized infected with spot and rust disease. The rust disease caused most severe damage on the mesophyll and vessel tissue.